The Information Science as a constituent part of Library and Information Science discipline during professional training at higher educational establishments in the USA (Pedagogy of Higher and Secondary Education, 2014)
Chukanova S. O. The Information Science as a constituent part of Library and Information Science discipline during professional training at higher educational establishments in the USA.The article is dedicated to the importance of Information Science as a part of Library and Information Science educational discipline in the USA.
Keywords: higher education in LIS; American Library Association; Library and Information Science; educational accreditation standards; information theory; professional training of future specialists